Neurosyphilis versus Herpes Encephalitis in a Patient with Confusion, Memory Loss, and T2-Weighted Mesiotemporal Hyperintensity. (16th February 2012) - Vedes, Elisa; Geraldo, Ana Filipa; Rodrigues, Rita; Reimão, Sofia; Ribeiro, Alice; Antunes, Francisco
Abstract : Acute confusion and memory loss associated with asymmetrical mesiotemporal hyperintensity on T2-weighted MRI are characteristic of herpes encephalitis. The authors report the case of a patient with these symptoms and MRI presentation who had neurosyphilis. Recently clinical and imaging patterns usually associated with herpes simplex encephalitis have been seen in patients with neurosyphilis. Because syphilis is "The Great Pretender" not only clinically but also in imaging and because its numbers are rising, it must be sought as a differential diagnosis.